2023
DOI: 10.3389/fpubh.2023.1210238
|View full text |Cite
|
Sign up to set email alerts
|

A review of neurological health disparities in Peru

Faris Almubaslat,
Sofia S. Sanchez-Boluarte,
Monica M. Diaz

Abstract: Peru is a historically unique and culturally diverse Latin American country. As a low-to-middle-income country (LMIC), Peru faces health implications from the spread of communicable diseases as well as a growing rate of noncommunicable diseases, both of which have been worsened by the recent COVID-19 pandemic’s impact on the national health system. Over the past two decades, the country has aimed to improve health access for its population through various efforts described in this review. Despite this, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 120 publications
0
0
0
Order By: Relevance
“…The prevalence of dementia among individuals aged 60 years and older is approximately 8.5% in Latin America 8 with projections indicating an increase from 7.8 million in 2013 to 27 million by 2050 9,10 . The Global Burden of Disease (GBD) study shows that neurodegenerative diseases in Peru, measured in Disability Adjusted Life Years (DALY), rose from the fifth to the third largest contributor to neurological diseases 11 . A recent study in Peru 12,13 found a 6.85% prevalence of dementia in 1,532 individuals over 65 in Lima, with Alzheimer’s disease (AD) as the predominant diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of dementia among individuals aged 60 years and older is approximately 8.5% in Latin America 8 with projections indicating an increase from 7.8 million in 2013 to 27 million by 2050 9,10 . The Global Burden of Disease (GBD) study shows that neurodegenerative diseases in Peru, measured in Disability Adjusted Life Years (DALY), rose from the fifth to the third largest contributor to neurological diseases 11 . A recent study in Peru 12,13 found a 6.85% prevalence of dementia in 1,532 individuals over 65 in Lima, with Alzheimer’s disease (AD) as the predominant diagnosis.…”
Section: Introductionmentioning
confidence: 99%